Metodologiczne problemy doskonalenia organizacji na podstawie nowych koncepcji zarządzania na przykładzie znormalizowanych systemów zarządzania - Kobyłko, Grzegorz (Methodological Problems in Organizations Improvement through New Management Conception the Example of Normalized Systems of Management, 2008)
The paper is an attempt to explain the rational implementation of normalized systems of management within organizations. The author carries out a critical analysis of theoretical possibility for organizations improvement through this concept. The author also gives recommendations on conditions for the correct implementation process of these systems. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 425-433